STRUKTUR MUSIK PULO PINANG DI DESA MENJALIN KECAMATAN MENJALIN KABUPATEN LANDAK - Robertus, Venansius; Djau, Nurmila Sari; Silaban, Chiristianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe lack of people’s interest in recognizing and learning traditional music, the inappropriateness of the beats modifications that eliminate its original beats, and the great effect of music creation that uses various beats rather than the traditional music that uses monotone beats have been the concern in this study. As a result, the traditional music that should be their identity has become neglected. The purpose of this thesis is to describe the music structure of Pulo Pinang in Menjalin Village, Menjalin District, Landak Regency and Describe the design of the results of research on the structure of Pulo Pinang music in the Menjalin Village, Menjalin District, Landak Regency in school. This is qualitative research using the descriptive method with the ethnomusicology approach. The data in this study were (1) the performance of Pulo Pinang music as competition in a traditional event Naik Dango, (2) Musical instrument Dau, Gong, Tuma’, and Solekng, and (3) the structure of Pulo Pinang music. themes, motifs, bars, scale, bars, tempo, dynamics, and phrases. The findings show that there are 4 musical instruments used in Pulo Pinang music. They are 8 units of Dau, 3 units of Gong, 1 unit of Tuma’, and 1 unit of Solekng. The music uses a block notation in the form of partiture. The result of the study was implemented into a lesson plan, providing a learning material discussing the history of Pulo Pinang music, the musical instruments used in the music, and the procedures of playing the musical instruments in the group. The results of this research can be applied to music art lessons for the subjects of Culture and Arts and Skills in VIII Middle School with Strandar Competencies.Keywords: Pulo Pinang, Music StructureAbstractThe lack of people’s interest in recognizing and learning traditional music, the inappropriateness of the beats modifications that eliminate its original beats, and the great effect of music creation that uses various beats rather than the traditional music that uses monotone beats have been the concern in this study. As a result, the traditional music that should be their identity has become neglected. The purpose of this thesis is to describe the music structure of Pulo Pinang in Menjalin Village, Menjalin District, Landak Regency and Describe the design of the results of research on the structure of Pulo Pinang music in the Menjalin Village, Menjalin District, Landak Regency in school. This is qualitative research using the descriptive method with the ethnomusicology approach. The data in this study were (1) the performance of Pulo Pinang music as competition in a traditional event Naik Dango, (2) Musical instrument Dau, Gong, Tuma’, and Solekng, and (3) the structure of Pulo Pinang music. themes, motifs, bars, scale, bars, tempo, dynamics, and phrases. The findings show that there are 4 musical instruments used in Pulo Pinang music. They are 8 units of Dau, 3 units of Gong, 1 unit of Tuma’, and 1 unit of Solekng. The music uses a block notation in the form of partiture. The result of the study was implemented into a lesson plan, providing a learning material discussing the history of Pulo Pinang music, the musical instruments used in the music, and the procedures of playing the musical instruments in the group. The results of this research can be applied to music art lessons for the subjects of Culture and Arts and Skills in VIII Middle School with Strandar Competencies. Keywords: Pulo Pinang, Music Structure